Construction of International Football Player Transfers to the Saudi Pro-league in BBC Sport News: A Framing Approach to Media Discourse (المجلة الدولية للبحوث العلمية, 2026)
This study examines how the international football player transfers to the Saudi Pro-league were framed in BBC Sport discourse during 2023. Drawing on a framing approach to discourse, thematic patterns, prominent social actors, and framing functions were investigated. The findings demonstrate that international football player transfers to the Saudi Pro-league were constructed through four main frames: Development and Change, Economic Investment, Sportswashing, and Threat and Danger. These frames are formed through the strategic allocation of voice to elite social actors, producing overlapping and sometimes contradictory evaluations of Saudi Arabia’s investment in football.  The study reveals that framing operates as a dynamic and contested process, reflecting broader tensions in Western media representations of non-Western modernization projects. By aligning the findings with Saudi Arabia’s Vision 2030 and soft power strategies, the article extends media framing research beyond Western contexts and offers insights into how national sports initiatives are negotiated and interpreted in international media discourse.